IDENTIFIKASI MORFOLOGI LARVA Anisakis sp PADA Epinephelus sp. DAN Rastrelliger sp DI PERAIRAN NTT - Sanam, Maxs U. E.; Detha, Annytha; Wuri, Diana; Dangga, Susana (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
The purpose of this research is to identify the level of intensity and degree of infection incidence of Anisakis sp in Rastrelliger sp and Epinephelus sp in eastern waters of Indonesia. A total of 190 fish specimens were randomized (random sampling) on ​​95 Rastrelliger sp and 95 Epinephelus sp from fish selling places in various areas of Kupang city. The larvae obtained were collected and fixed with 70% alcohol, and stained using Semichen acetic carmine solution. Morphological identification of Anisakis sp larvae through ventriculus, boring tooth, and mucron shapes on a stereo microscope. The parasites found were grouped into Anisakis sp type I and type II. Based on the results of the study, it was found that the presence of Anisakis sp. in Epinephelus sp that is 94 out of 95 fish. The results also confirmed that Anisakis sp infection implies a high risk of Epinephelus sp fish species so that further identification is needed at the molecular level.